Teacher self-efficacy of primary school teachers working in Irish ASD classes. Issue 2 (4th March 2022) - Ryan, Amy; Mathews, Elizabeth S.
ABSTRACT: This study investigated the perceived Teacher Self-Efficacy (TSE) of primary school teachers in Ireland who are working in special classes for students with autism. Furthermore, it sought to examine whether these perceptions of TSE were related to special class teaching experience, their engagement in professional development pertaining to autism, and their perceptions of principals' instructional support. An online questionnaire was administered to 139 of these teachers. The findings indicated that participants had a relatively high sense of TSE. Correlation analyses identified statistically significant, positive correlations between the three independent variables and the dependent variable of TSE.